2002
DOI: 10.1080/713603159
|View full text |Cite
|
Sign up to set email alerts
|

The pathophysiological influence of leptin and the tumor necrosis factor system on maternal insulin resistance: negative correlation with anthropometric parameters of neonates in gestational diabetes

Abstract: The contribution of the tumor necrosis factor (TNF) system and leptin was studied in insulin resistance and neonatal development during the course of normal pregnancy and gestational diabetes mellitus (GDM). Thirty patients with GDM and their neonates (n = 30), 35 healthy pregnant women (15 in the first, nine in the second and 11 in the third trimester) and their neonates (n = 20), and 25 healthy matched non-pregnant women participated in the study. Significantly elevated levels of maternal TNF-alpha, sTNF rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
4
33
1
1
Order By: Relevance
“…Correlations have been found among plasma leptin level, BMI and adipose tissue mass (particularly subcutaneous fat) in both animals and non-pregnant adults (Hamilton et al 1995, Lonnqvist et al 1995, Cseh et al 2002. Similarly, in this study, the release of leptin from adipose tissue strongly correlated with maternal body weight and BMI.…”
Section: Discussionsupporting
confidence: 54%
“…Correlations have been found among plasma leptin level, BMI and adipose tissue mass (particularly subcutaneous fat) in both animals and non-pregnant adults (Hamilton et al 1995, Lonnqvist et al 1995, Cseh et al 2002. Similarly, in this study, the release of leptin from adipose tissue strongly correlated with maternal body weight and BMI.…”
Section: Discussionsupporting
confidence: 54%
“…Given that there are possible important roles for the adipocytokines in the early defects of type 2 diabetes, GDM women represent an ideal population to study these inter-relationships further. To date, there is limited cross-sectional information that TNFα may be elevated in GDM pregnancy [4,10]. Other cross-sectional reports have shown that adiponectin levels are reduced in women with GDM [6,7,11,12].…”
mentioning
confidence: 99%
“…A maximum dose of 20 g was used during pregnancy and 25 g postpartum (in order to not overestimate the glucose dose based on a late pregnancy weight) and the cannula flushed with 20 mL of normal saline immediately after the IV dextrose. Samples were drawn from the same cannula at 2, 3,4,6,8,10,15,20,30,40,60,75,90 and 120 min, with flushing of the cannula with 3 mL of normal saline between each draw [17]. Samples were placed into pre-chilled tubes (serum/EDTA for TNFα, Ad, high sensitivity CRP (hsCRP), leptin and lipids; 4% sodium fluoride 25 µL/mL blood for glucose and insulin), centrifuged within 40 min and stored at −80 • C until time of assay.…”
Section: Experimental Designmentioning
confidence: 99%
“…GDM is considered a prediabetic state, therefore it may display many abnormalities that possibly appear in the very early stages of type 2 diabetes mellitus (T2DM) (Pendegrass et al, 1995). In addition to mechanisms similar to patients with T2DM (Friedman et al, 1999 andCatalano et al, 2002), the etiopathogenesis of GDM includes the combination of the disturbed endocrine function of adipose tissue and placenta (Coughlan et al, 2001;Cseh et al, 2002;Kirwan et al, 2002;Radaelli et al, 2003;Ranheim et al, 2004 andMeller et al, 2006), and the systemic hormonal changes affecting insulin sensitivity in peripheral tissues .…”
Section: Introductionmentioning
confidence: 99%